EFFECT OF WORKPLACE ERGONOMICS ON EMPLOYEE JOB SATISFACTION OF SELECTED TIER–ONE DEPOSIT MONEY BANKS IN IKEJA LOCAL GOVERNMENT, LAGOS - ADEKOYA, EMMANUEL OLAWALE; JAYEOBA, FOLUSO ILESANMI; FAPOHUNDA, TINUKE MORADEKE (Scholars Digest Publishing, 2022)
The interrelationship between workplace ergonomics and employee job satisfaction has become a major concern among professionals and human resource experts in the banking sector. Deposit money banks seemingly experiences challenges of poor workplace ergonomic in terms of high repetitive tasks and insufficient rest time which in turn adversely affect employee job satisfaction. However, the study examined the effect of workplace ergonomic (physical workplace environment, high repetitive tasks and allowable break time) on employees’ job satisfaction of Tier-1 deposit money banks in Ikeja Local Government, Lagos State. This study employed survey research design and collected data from one hundred and sixty-nine (169) respondents whose questionnaire were well completed and used for data analysis using simple random sampling method. Three hypotheses were tested using simple regression statistics with the aid of SPSS version 25.0. Findings revealed that physical workplace environment and high repetitive tasks have positive and significant effect on employee job satisfaction while allowable break time has negative and significant effect on employee job satisfaction of Tier-1 deposit money banks in Ikeja Local Government, Lagos State. It was concluded that workplace ergonomic (physical workplace environment, high repetitive tasks and allowable break time) affect employees’ job satisfaction of Tier-1 deposit money banks in Ikeja Local Government, Lagos State. Thus, the study recommended among other things that the management should entice the employees by providing conducive physical workplace facilities, reduce high repetitive tasks and provide sufficient rest time. By so doing, the job satisfaction of employees would be enhanced.